PERAN PPL DALAM IMPLEMENTASI KEGIATAN KOKURIKULER MENGHAFAL SURAT-SURAT PENDEK AL-QUR’AN MELALUI METODE GERAKAN TANGAN DI SDN 1 GENTENG WETAN BANYUWANGI - Sudarsri Lestari; Imam Wahyono (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2019)
Kokurikuler activities are intended to further deepen and appreciate the subject matter that has been learned in intracurricular activities in the classroom. In grade IV elementary school subjects there is material about memorizing short letters in the Qur'an. If it is associated with the cognitive development stage of elementary school students who are still in the concrete operational stage, the material for memorizing short letters in the Qur'an is still difficult for students to understand because it is still abstract. In order to facilitate and understand the material of memorizing short letters in the Qur'an, the teacher needs a method of hand movements so that the letters are not only memorized but also can be understood by the students. The activity of memorizing the Qur'an's short letters with hand gestures is part of the form of dedication carried out at SDN 1 Genteng Wetan. The method of hand movements carried out by the child is in accordance with the meaning, so that the child knows the meaning of each verse. The application of the hand movement method is not boring for children. Through this method the child does not have to sit and listen and repeat reading. Learning activities with movement, playing, verse reciting quizzes, and giving each child the opportunity to practice.